Exploring Palmaria palmata as a dietary ingredient for European sea bass (Dicentrarchus labrax) juveniles - Catarina Ramos-Oliveira; Rui Magalhães; Lúcia Vieira; Helena Fernandes; Isabel Belo; Aires Oliva-Teles; Helena Peres (Aquaculture International, 2026)
The red macroalgae Palmaria palmata is rich in protein and bioactive compounds and has been identified as a promising dietary ingredient for aquafeeds, with the potential to partially replace selected plant-based feed components. A digestibility trial and a growth trial were conducted to evaluate the potential of untreated and pretreated P. palmata as feed ingredients for juvenile European seabass ( Dicentrarchus labrax ), with initial body weights of 63.2 g and 38.0 g, respectively. Five diets were formulated: a control diet without macroalgae, and four diets including either 7.5% or 15% of untreated and pretreated P. palmata , replacing plant ingredients. The apparent digestibility coefficients of dry matter, crude protein, lipids, and gross energy did not differ among diets. The dietary inclusion of up to 15% P. palmata significantly increased the growth performance and feed efficiency compared to the control diet, without affecting nutrient digestibility, digestive enzyme activities, plasma metabolites, or whole-body composition of the fish. The pretreatment applied to P. palmata significantly increased soluble protein content and decreased neutral detergent fiber, but did not further improve growth or feed efficiency. Overall, these results indicate that up to 15% P. palmata can be successfully incorporated into the diets of juvenile European seabass, improving growth performance without adverse effects on nutrient digestibility. Further work is required to evaluate the functional properties and implications for fish health of P. palmata as well as to assess its economic viability within commercial aquafeed formulations.

Disentangling the effects of herbivore pressure, seasonality, and landscape structure on the abundance and body condition of mediterranean small mammals - Mariana Rossa; Luís M. Rosalino; Sofia Sabino; Antonio J. Carpio; Eduardo Ferreira; Joana Fernandes; Paloma Linck; Jorge F. Henriques; Rita Tinoco Torres; Rui G. Morgado; João Carvalho (Mammalian Biology, 2026)

High-solid loading alkaline autoclaved-processed Codium tomentosum as a sustainable feed ingredient for juvenile european seabass (Dicentrarchus labrax) - Catarina Ramos-Oliveira; Rui Magalhães; Lúcia Vieira; Helena Fernandes; Isabel Belo; Aires Oliva-Teles; Helena Peres (Journal of Applied Phycology, 2026)
Codium tomentosum , a marine green macroalga is also produced in integrated multi-trophic aquaculture (IMTA) systems; however, its use in aquafeeds remains unexplored. This study evaluated the potential of C. tomentosum as a feedstuff for European seabass ( Dicentrarchus labrax ) and, for the first time, applied a high-solid-loading alkaline autoclave pre-treatment to enhance its nutritional value. Macroalgal biomass was treated with 1N NaOH (75% moisture) at 121 °C for 30 or 60 min, producing a slurry hydrolysate that was dried and incorporated at 7.5% into experimental diets. Four diets were tested in triplicate: a control diet, with no incorporation of C. tomentosum , a diet with untreated C. tomentosum (COD), and two diets including pre-treated C. tomentosum for 30 min (COD30) or 60 min (COD60). Two trials were performed: a digestibility trial (initial bodt weight (IBW) = 63 g) and an 11-week feeding trial with European seabass (IBW = 38 g) fed to apparent satiation. Inclusion of untreated C. tomentosum increased apparent digestibility but did not affect growth performance or feed efficiency. In contrast, fish fed the COD30 diet showed higher protein and amino acid digestibility and improved growth performance, feed utilization, and protein efficiency ratio compared with both control and untreated C. tomentosum diets. Extending the pre-treatment to 60 min did not lead to additional benefits and tended to reduce digestibility, feed intake, and growth. Whole-body composition and plasma biochemical parameters did not differ among treatments. Overall, a 30-min high solid-loading alkaline autoclave pre-treatment of C. tomentosum enhanced nutrient digestibility, growth, and feed utilization, supporting its potential as a sustainable ingredient in aquafeeds.

Effect of soil fertilization on wood quality in clonal and seminal planting of Eucalyptus dunnii - Wesley Santos de Jesus; Thiago de Campos Monteiro; Tauana de Souza Mangini; Alessandro Camargo Ângelo; Rui André Maggi dos Anjos; Alan Sulato de Andrade; Renato Cesar Gonçalves Robert; Allan Motta Couto; Karen Koch Fernandes de Souza (Journal of the Indian Academy of Wood Science, 2026)
The aim of this work was to evaluate the effect of soil mineral fertilization in clonal and seminal plantations of E. dunnii on wood quality and its relationship with tree crown and trunk variables. Data were collected in experimental plantations of E. dunnii at 8.5-years-old. The treatments were seminal and clonal propagation and soil fertilization: conventional formulation, slow-release, and control. Tree crown and trunk variables were measured. Tree grain deviation, growth stress (LRS) and wood density were also measured. A mean test to compare treatments was performed and a correlation test was performed between parameters. Principal component analyzes (PCAs) were generated to understand the effects of treatments. The results demonstrate that the seminal propagation presented a greater length and percentage of the tree crown. On the other hand, clonal trees showed higher LRS. Soil fertilized in plantations showed a lower degree of trunk slenderness rate. The LRS showed a positive correlation with the trunk dimensions and volume. The PCAs results recommend the planting of clonal E. dunnii , under the soil nutritional management with fertilization of conventional formulation. These trees tend to present greater trunk growth and volumetric increment, as well as better parameters wood quality variables.

TS_Predictor: a deep learning toolbox for GNSS time series prediction with signal decomposition and nonlinear modelling - Xiaoxing He; Yu Zhou; Jun Li; Gaël Kermarrec; Rui Fernandes; Jean-Philippe Montillet; Shuangcheng Zhang; Shunqiang Hu (Advances in Space Research, 2026)

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Deciphering the potential of orange peel polysaccharides for modulating black tea astringency - Joana Vieira; Inês E. Silva; Carlos Guerreiro; Carlo Bravo; Alessandra Rinaldi; Rui M. Ramos; Pedro A.R. Fernandes; Manuel A. Coimbra; Virgínia Cruz Fernandes; Victor de Freitas; Elsa Brandão; Susana Soares (Food Hydrocolloids, 2026)

Quercetin mitigates pro-inflammatory effects of polyvinylpyrrolidone-coated silver nanoparticles on human intestinal epithelial cells - Adelaide Sousa; Inês Santos; Rui Fernandes; Sofia Pacheco; Félix Carvalho; Eduarda Fernandes; Marisa Freitas (Toxicology in Vitro, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

Are all nanoplastics equally neurotoxic? Influence of size and surface functionalization on the toxicity of polystyrene nanoplastics in human neuronal cells - Carolina Mota; Ana Margarida Araújo; Maria Enea; Eulália Pereira; Ana Reis-Mendes; Rui Fernandes; Sofia Pacheco; Marlene Lúcio; Carla Martins Lopes; Isabel M.P.L.V.O. Ferreira; Márcia Carvalho (Environmental Pollution, 2026)

Treatment of natural dye wastewaters by electrochemical oxidation: Comparative analysis of anode materials and optimization for reuse - Bárbara Saraiva; Nuno Belino; Rui Miguel; Víctor López-Grimau; Valentina Buscio; João Carvalho; Annabel Fernandes (Journal of Environmental Management, 2025)

Molecular dynamics of Lys49 PLA2-like toxins: Insights into solution and membrane-bound conformations - Rui Rachão; João T.S. Coimbra; Maria J. Ramos; José-María Gutiérrez; Bruno Lomonte; Pedro A. Fernandes (Toxicon, 2025)

Photocatalytic removal of pollutants via exfoliated carbon nitride: Advances and challenges - Eryk Fernandes; Rui C. Martins; João Gomes (Journal of Environmental Chemical Engineering, 2025)

Cerium oxide integration and oxygen doping of g-C₃N₄ for boosted solar removal of emerging pollutants and water disinfection - Eryk Fernandes; Paweł Mazierski; Magdalena Miodyńska-Melzer; Kostiantyn Nikiforow; Tomasz Klimczuk; Adriana Zaleska-Medynska; Rui C. Martins; João Gomes (Chemical Engineering Journal, 2025)

Impact of wildfire emissions exposure on the associations between levels of lung injury, lipid peroxidation, DNA oxidation, and exposure biomarkers - Bela Barros; Ana Margarida Paiva; Rui Azevedo; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; João Paulo Teixeira; Solange Costa; Agostinho Almeida; et al. (Science of The Total Environment, 2025)

Optimization of bacterial biomass production using soybean molasses-based medium as a potential component for bean crop inoculant development - Ana Cristina Silva da Natividade; Rui dos Santos Ferreira Filho; Janaína Fernandes de Medeiros Burkert; Carlos André Veiga Burkert (Biocatalysis and Agricultural Biotechnology, 2025)

Growth, oxidative stress, and intermediary metabolism of European seabass (Dicentrarchus labrax) juveniles fed diets including solid-state fermented distiller's dried grains with solubles - Diogo Filipe; Rui Magalhães; Helena Fernandes; José Manuel Salgado; Isabel Belo; Aires Oliva-Teles; Helena Peres (Animal Feed Science and Technology, 2025)

Screening for microplastics in agricultural soils: Applying green chemistry principles in extraction and analysis - Diana Rede; Rui Vilarinho; Joaquim Agostinho Moreira; Luca Nizzetto; Cristina Delerue-Matos; Virgínia Cruz Fernandes (Environmental Pollution, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Exploring quercetin's protective potential against the pro-inflammatory effects of silver nanoparticles in C57BL/6J mice - Adelaide Sousa; Andreia Amaro; Vera Marisa Costa; Rui Azevedo; Sara Oliveira; Sofia Viana; Flávio Reis; Agostinho Almeida; Paulo Matafome; Patrícia Dias-Pereira; Félix Carvalho; Eduarda Fernandes; et al. (Food and Chemical Toxicology, 2025)

Application of the pair-input deep learning model for seismicity reassessment in Cameroon - Luis Carvalho; Hamzeh Mohammadigheymasi; Paul Crocker; Nasrin Tavakolizadeh; Yahya Moradichaleshtori; Rui Fernandes (Acta Geophysica, 2024)
Applying advanced signal analysis and feature extraction methods to seismic datasets facilitates the extraction of key information from these valuable resources. In particular, advanced deep learning models can play a crucial role in this extraction process from seismic waveforms. This study aims to analyze the seismicity of the Cameroon area by deeply scanning an archived dataset from a temporary seismic network composed of 32 broadband sensors that operated in Cameroon from March 2005 to February 2007. We thoroughly scan the dataset to detect local earthquakes, calculate an updated crustal velocity model for the region by incorporating the acquired earthquake bulletin, and perform a joint inversion scheme. The DL-based workflow implemented in this study utilizes a pair-input deep learning model for scanning the seismic phases in the dataset, followed by a seismic phase picking process. Applying the Rapid Earthquake Association and Location method allows for the association of detected phases with local seismic events. By combining a set of 17,261 P-picked and 14,239 S-picked phases associated with 473 well-located earthquakes with magnitudes ranging from $$1.3 \le M_L \le 4.6$$ 1.3 ≤ M L ≤ 4.6 , we implement a joint inversion to estimate an updated 1D crustal velocity model and hypocentral parameters. The obtained model reveals layers with thicknesses of 82,034, and 54 km, extending to a depth of 80 km, with P-wave velocities ( $$V_{{\text{p}}}$$ V p ) of 6.1, 6.4, 6.6, 7.6, 8.25, and 8.5 km/s, and S-wave velocities ( $$V_{{\text{s}}}$$ V s ) of 3.57, 3.74, 3.86, 4.44, 4.82, and 5.0 km/s, respectively. The newly detected seismic events predominantly cluster in the Central Cameroon Shear Zone (CCSZ), the east flank of Mount Cameroon, the region between Mount Cameroon and Bioko Island, and the southern part of Bioko Island. The validity of this approach is further supported by a newly compiled catalog for this period, which is 1.35 times more extensive than the previously reported catalog for this dataset. Finally, the study presents a 3D time-lapse animation illustrating the sequence of detected earthquakes.

Biomonitoring of firefighters' exposure to priority pollutant metal(loid)s during wildland fire combat missions: Impact on urinary levels and health risks - Ana Margarida Paiva; Bela Barros; Rui Azevedo; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; Maria do Carmo Pereira; João Paulo Teixeira; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Effect of coconut processing by-product graded feeding on carcass traits and meat quality of lambs - Felipe J.S. Silva; Dorgival M. Lima Júnior; Beatriz D.O. Fernandes; Anaiane P. Souza; Susana P. Alves; Rui J.B. Bessa; Francisco F.R. Carvalho; Ariosvaldo N. Medeiros (Meat Science, 2024)

Investigating the impact of microplastics on triphenyl phosphate adsorption in soil: Insights into environmental factors and soil properties - Diana Rede; Rui Vilarinho; Joaquim Agostinho Moreira; Cristina Delerue-Matos; Virgínia Cruz Fernandes (Science of The Total Environment, 2024)

Effect of solid-state fermentation of Brewer's spent grain on digestibility and digestive function of european seabass (Dicentrarchus labrax) juveniles - Tássia Estevão-Rodrigues; Helena Fernandes; Sara Moutinho; Diogo Filipe; Filipa Fontinha; Rui Magalhães; Ana Couto; Marta Ferreira; Margarida Gamboa; Carolina Castro; Isabel Belo; José Salgado; et al. (Animal Feed Science and Technology, 2024)

Cork oak woodlands and decline: a social-ecological review and future transdisciplinary approaches - Margarida Lopes-Fernandes; Ernesto Martínez-Fernández; Rui Alves; Daniel Boa-Nova; Cristina Branquinho; Miguel N Bugalho; Felipe Campos-Mardones; Agustin Coca-Pérez; Amélia Frazão-Moreira; Marco Marques; Javier Moreno-Ortiz; Octávio Paulo; et al. (Agroforestry Systems, 2024)
Cork oak woodlands are socio-ecosystems recognized as biodiversity hotspots, a fundamental economic source for companies and local communities as well as an identitarian landscape for residents and visitors. Cork oak woodlands, however, are facing tree mortality and lack of regeneration. Considering the oak decline scenario, we present Iberian cork oak montado/dehesa as a socio-ecosystem facing climate change, management transformations, local knowledge crisis and social uncertainty. We review montado s/ dehesa s research through time and by different scholar perspectives. We defend that from an interdisciplinary and transdisciplinary perspective, including the experience and evidence observed in terrain, debate should be stimulated, and novel conceptual approaches may contribute to finding solutions. We argue that the confluence of ecology, genetics, anthropology and local knowledge can be explored to unveil the complexities and the challenges of these socio-ecosystems and contribute to prevent and mitigate threats to it. We propose a methodological approach built together with scientists, managers and workers, that can explore oak translocations, socio-ecological interactions models, knowledge transfer and other ways to overcome Iberian cork oak woodlands socio-environmental crisis.

Pollutant-meteorological factors and cardio-respiratory mortality in Portugal: Seasonal variability and associations - Ediclê de Souza Fernandes Duarte; Paulo Sérgio Lucio; Maria João Costa; Vanda Salgueiro; Rui Salgado; Miguel Potes; Judith J. Hoelzemann; Daniele Bortoli (Environmental Research, 2024)

Effects of diets differing in the concentrate-to-roughage ratio on meat quality and fatty acids composition in abomasal digesta and meat from thin-tail and fat-tail Brazilian ovine breeds - Luana França dos Anjos; Rui José Branquinho de Bessa; Henrique Nunes Parente; Susana Paula Alves; Aline Vieira Landim; Anderson de Moura Zanine; Anderson Lopes Pereira; Graziele Silva de Oliveira; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Mayara Raposo dos Santos; Michelle de Oliveira Maia Parente (Small Ruminant Research, 2023)

Future distribution patterns of nine cuttlefish species under climate change - Miguel Fernandes Guerreiro; Francisco Oliveira Borges; Catarina Pereira Santos; Rui Rosa (Marine Biology, 2023)
While most coastal communities are expected to, or have been, negatively impacted by climate change, cephalopods have generally thrived with shifting ocean conditions. However, whilst benefitting from the same physiological flexibility that characterizes cephalopods in general, cuttlefish have depth constraints imposed by the presence of a cuttlebone and are limited to specific locations by their particularly low vagility. To evaluate the potential effects of marine climate change on cuttlefish, Species Distribution Models (SDM) were applied to nine species of genus Sepiidae to assess potential changes to their future distribution (2050 and 2100), under four representative concentration pathway (RCP) scenarios (i.e., RCP 2.6, 4.5, 6.0, and 8.5; CMIP5). We show that future cuttlefish habitat suitability and distribution will potentially decrease. The species with the most extreme impacts, Doratosepion braggi (Verco, 1907), was observed to decline as much as 30.77% in average habitat suitability (from present 55.26% to 24.48% at RCP 8.5 in 2100), to Sepia officinalis Linnaeus, 1758 with a low maximum decrease of 1.64% in average habitat suitability (from present 59.62% to 57.98% at RCP 8.5 in 2100). Increases in habitat suitability were projected mostly at higher latitudes, while habitat decrease was predicted for the tropical regions and lower latitudinal limits of species’ distributions. As their habitats decrease in terms of habitat suitability, cuttlefish may not benefit from future changes in climate. Additionally, as potential “sea canaries” for coastal ecosystems, we may see many species and habitats from these systems affected by climate change, particularly in tropical regions.

Mapping socio-environmental pressures to assess Portuguese soil vulnerability - Concha Cano-Díaz; Romy Zeiss; Claudia Carvalho-Santos; Rui P. Carvalho; Sofia R. Costa; A. Carolina Duarte; Paulo Fernandes; Carlos A. Guerra (Applied Geography, 2023)

Carbon nitride exfoliation for photocatalysis and photocatalytic ozonation over emerging contaminants abatement - Eryk Fernandes; Pawel Mazierski; Magdalena Miodyńska; Tomasz Klimczuk; Mirosława Pawlyta; Adriana Zaleska-Medynska; Rui C. Martins; João Gomes (Journal of Environmental Chemical Engineering, 2023)

Quality and sensory milk traits of goats grazing Caatinga or confined receiving either corn or spineless cactus-based diets in the Brazilian semiarid environment - Beatriz Dantas Oliveira Fernandes; Susana Paula Almeida Alves; Rita de Cássia Ramos do Egypto Queiroga; Alberício Pereira de Andrade; Divan Soares da Silva; Luana Magna de Souza; Anaiane Pereira Souza; Rui José Branquinho Bessa; Ariosvaldo Nunes de Medeiros (Tropical Animal Health and Production, 2023)

Impact of climate change on the distribution and habitat suitability of the world’s main commercial squids - Miguel Fernandes Guerreiro; Francisco Oliveira Borges; Catarina Pereira Santos; José Carlos Xavier; Henk-Jan Hoving; Rui Rosa (Marine Biology, 2023)
Climate change is expected to have major negative effects on marine life across phylogenetic groups. Cephalopods, however, have life history characteristics that suggest they may benefit from certain climate change scenarios. Of all cephalopods, squids reach the greatest biomasses; as a result, they are of substantial importance for human and predator consumption. To test the hypothesis that the effects of climate change are beneficial for commercial squid, we used species distribution models on climate scenarios for the period between 2000 and 2014, as well as the years 2050 and 2100 (RCP [representative concentration pathway] 2.6, 4.5, 6.0, and 8.5; CMIP5). Our results suggest that consequences of climate change scenarios are species specific. In the North Pacific and Northwest Atlantic, squid’s habitat suitability may increase (from + 0.83% [ Doryteuthis pealeii ] to + 8.77% increase [ Illex illecebrosus ]), while it is predicted to decrease in other regions (from − 1.03% [ Doryteuthis opalescens ] to − 15.04% decrease [ Loligo reynaudii ]). Increases in habitat suitability occurred mostly at higher latitudes (north of 50° N), while suitable habitat decrease was predicted for the tropical regions. These shifts in future habitat suitability were stronger under harsher emission scenarios. Starting in 2050 (with RCP scenarios 4.6, 6.0 and 8.5), as a result of warming of the Arctic, squid habitat may increase along both coasts of North America. In the Southern Hemisphere, squids may lose habitat with no poleward habitat alternatives to move into. Contrary to our hypothesis, these commercial squid do not stand to benefit from climate change. Since these squid are an important food source for marine megafauna and humans, it is imperative that climate change biogeographic impacts are considered for a sustainable management of this important group of molluscs.

Biodistribution and intestinal inflammatory response following voluntary oral intake of silver nanoparticles by C57BL/6J mice - Adelaide Sousa; Rui Azevedo; Vera Marisa Costa; Sara Oliveira; Inês Preguiça; Sofia Viana; Flávio Reis; Agostinho Almeida; Paulo Matafome; Patrícia Dias-Pereira; Félix Carvalho; Eduarda Fernandes; et al. (Archives of Toxicology, 2023)
Silver nanoparticles (AgNP) are among the most widely commercialized nanomaterials globally, with applications in medicine and the food industry. Consequently, the increased use of AgNP in the food industry has led to an unavoidable rise in human exposure to these nanoparticles. Their widespread use raises concerns about potential hazards to human health, specifically their intestinal pro-inflammatory effects. Thus, the main objective of this study was to evaluate the biological effects of two subacute doses of 5 nm polyvinylpyrrolidone (PVP)-AgNP in C57BL/6J mice. One mg/kg body weight or 10 mg/kg bw was provided once a day for 14 days, using a new technology (HaPILLness) that allows voluntary, stress-free, and accurate oral dosing. It was observed that after oral ingestion, while AgNP is biodistributed throughout the entire organism, most of the ingested dose is excreted in the feces. The passage and accumulation of AgNP throughout the intestine instigated a prominent inflammatory response, marked by significant histological, vascular, and cellular transformations. This response was driven by the activation of the nuclear factor-кB (NF-кB) inflammatory pathway, ultimately leading to the generation of multiple cytokines and chemokines.

Low-cost materials for swine wastewater treatment using adsorption and Fenton’s process - Eva Domingues; João Lincho; Maria J. Fernandes; João Gomes; Rui C. Martins (Environmental Science and Pollution Research, 2023)
Untreated swine wastewater (SW) discharge leads to serious consequences such as water quality decreasing related to eutrophication and proliferation of harmful algae containing cyanotoxins, which can cause acute intoxication in humans. The use of untreated pig farming effluent as fertilizer can lead to the accumulation of polluting compounds. Biological treatments can degrade organic matter but have the disadvantage of requiring large areas and high retention times and demonstrating low efficiencies in the degradation of refractory compounds such as pharmaceutical compounds. In this ambit, the performance of four low-cost materials was evaluated for treatment of a swine wastewater using physical–chemical processes such as adsorption and Fenton’s process. The tested materials are two natural resources, red volcanic rock from Canary (RVR) Islands and black volcanic rock (BVR) from Azores, and two industry residues, red mud (RM) and iron filings (IF). Among the tested materials, only IFs are catalytically active for Fenton’s peroxidation. Still, RVR, BVR, and RM were efficient adsorbents removing up to 67% of COD. The combination between adsorption followed by Fenton’s process using IF as catalyst showed interesting results. When RM is applied as adsorbent in the diluted effluent, it was able to remove 67% and 90% of COD for adsorption and adsorption followed by IF Fenton, respectively. At those conditions, the resultant treated effluent accomplishes the requirements for direct discharge in the natural water courses as well as the parameters for water reusing.

Solid-State Fermentation of Distiller’s Dried Grains with Solubles Improves Digestibility for European Seabass (Dicentrarchus labrax) Juveniles - Diogo Filipe; Mário Dias; Rui Magalhães; Helena Fernandes; José Salgado; Isabel Belo; Aires Oliva-Teles; Helena Peres (Fishes, 2023)
Aquaculture requires new, economical, and eco-friendly protein sources to replace traditional fisheries and plant ingredients. Using agriculture by-products as protein sources would reduce land-based feed production pressure and waste production, promoting a circular economy and sustainable aquaculture. Distiller’s dried grains with solubles (DDGS) is the main by-product of bioethanol production. Corn DDGS has a high protein level, but its high fiber content limits its use as a feed ingredient, particularly for carnivorous fish. Solid-state fermentation (SSF) uses lignocellulosic-rich substrates, such as DDGS, for microbial growth in the near absence of water, promoting enzyme production that degrades the lignocellulosic matrix, increasing free reducing sugars, protein, and antioxidant levels of the substrate. In the present work, the SSF of corn DDGS with Aspergillus carbonarius, A. ibericus, and A. uvarum was tested. Then, the digestibility of the most promising fermented DDGS (in terms of upgraded nutritional composition) was tested by including it in a reference diet (70% of a reference diet; 48% crude protein; 15% crude lipids) for European seabass (Dicentrarchus labrax) juveniles (171 g averaged weight; trial duration of 52 days). Among the fungi tested, Aspergillus ibericus led a generally higher upgrading of the DDGS nutritional composition, leading to a high amount of protein (from 42.7 to 49.7 g N/kg DM), phenolic compounds (1.49 to 4.86 mg/g caffeic acid equivalents), free sugars (9.5 to 31.9 mg/g), and enzyme production (45 U/g and 68 U/g of cellulase and xylanase, respectively), and a high reduction in acid detergent fiber and neutral detergent fiber content (up to 29 and 43%, respectively). Compared to the unfermented DDGS, fermented DDGS presented increased protein, lipids, starch, and energy digestibility, while phosphorous digestibility was similar. Compared to the reference diet, dietary inclusion of unfermented or fermented DDGS increased trypsin and chymotrypsin activities. The activity of digestive enzymes was not affected by the inclusion of fermented DDGS, except for amylase activity, which was lower with the fermented DDGS than with the unfermented DDGS diet. In conclusion, SSF of DDGS enhanced its nutritional value, increasing DDGS digestibility when included in diets for European seabass juveniles.

Silver nanoparticles exert toxic effects in human monocytes and macrophages associated with the disruption of Δψm and release of pro-inflammatory cytokines - Adelaide Sousa; Ana T. Rufino; Rui Fernandes; Ana Malheiro; Félix Carvalho; Eduarda Fernandes; Marisa Freitas (Archives of Toxicology, 2023)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

Removal pattern of vinasse phenolics by Phlebia rufa, characterization of an induced laccase and inhibition kinetics modeling - Joana M. C. Fernandes; Irene Fraga; Rui M. F. Bezerra; Albino A. Dias (Biodegradation, 2021)

Designer Cathinones N-Ethylhexedrone and Buphedrone Show Different In Vitro Neurotoxicity and Mice Behaviour Impairment - Cristina de Mello-Sampayo; Ana Rita Vaz; Sara C. Henriques; Adelaide Fernandes; Fabiana Paradinha; Pedro Florindo; Paulo Faria; Rui Moreira; Dora Brites; Alvaro Lopes (Neurotoxicity Research, 2021)

Effect of Duration of Exposure to Fluoride and Type of Diet on Lipid Parameters and De Novo Lipogenesis - Aline Dionizio; Heloisa Aparecida Barbosa Silva Pereira; Tamara Teodoro Araujo; Isabela Tomazini Sabino-Arias; Mileni Silva Fernandes; Karina Aparecida Oliveira; Fabielle Sales Raymundo; Tânia Mary Cestari; Fernando Neves Nogueira; Rui Albuquerque Carvalho; Marília Afonso Rabelo Buzalaf (Biological Trace Element Research, 2019)

Noise-Dependent Adaption of the Wiener Filter for the GPS Position Time Series - Anna Klos; Machiel S. Bos; Rui M. S. Fernandes; Janusz Bogusz (Mathematical Geosciences, 2019)

Population genetics of the bigeye thresher shark Alopias superciliosus in the Atlantic and Indian Oceans: implications for conservation - Millke Jasmine Arminini Morales; Fernando Fernandes Mendonça; Carolina Oliveira Magalhães; Claudio Oliveira; Rui Coelho; Miguel Neves Santos; Vanessa Paes Cruz; Andrew Piercy; George Burgess; Fabio Vieira Hazin; Fausto Foresti (Reviews in Fish Biology and Fisheries, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The role of fire-suppression force in limiting the spread of extremely large forest fires in Portugal - Paulo M. Fernandes; Abílio Pereira Pacheco; Rui Almeida; João Claro (European Journal of Forest Research, 2016)

Effects of fish oil replacement by vegetable oil blend on digestive enzymes and tissue histomorphology of European sea bass (Dicentrarchus labrax) juveniles - Carolina Castro; Ana Couto; Amalia Pérez-Jiménez; Cláudia R. Serra; Patricia Díaz-Rosales; Rui Fernandes; Geneviève Corraze; Stéphane Panserat; Aires Oliva-Teles (Fish Physiology and Biochemistry, 2016)

Assessment of environment, land management, and spatial variables on recent changes in montado land cover in southern Portugal - Sérgio Godinho; Nuno Guiomar; Rui Machado; Pedro Santos; Paulo Sá-Sousa; J. P. Fernandes; Nuno Neves; Teresa Pinto-Correia (Agroforestry Systems, 2016)

Contributions of hydrogeophysics to the hydrogeological conceptual model of the Albufeira-Ribeira de Quarteira coastal aquifer in Algarve, Portugal - Alain P. Francés; Elsa C. Ramalho; Judite Fernandes; Michel Groen; Rui Hugman; Mohamed A. Khalil; Joel De Plaen; Fernando A. Monteiro Santos (Hydrogeology Journal, 2015)

Using species richness and functional traits predictions to constrain assemblage predictions from stacked species distribution models - Manuela D'Amen; Anne Dubuis; Rui F. Fernandes; Julien Pottier; Loïc Pellissier; Antoine Guisan (Journal of Biogeography, 2015)
Aim Modelling species distributions at the community level is required to make effective forecasts of global change impacts on diversity and ecosystem functioning. Community predictions may be achieved using macroecological properties of communities (macroecological models, MEM ), or by stacking of individual species distribution models (stacked species distribution models, S‐ SDM s). To obtain more realistic predictions of species assemblages, the SESAM (spatially explicit species assemblage modelling) framework suggests applying successive filters to the initial species source pool, by combining different modelling approaches and rules. Here we provide a first test of this framework in mountain grassland communities. Location The western Swiss Alps. Methods Two implementations of the SESAM framework were tested: a ‘probability ranking’ rule based on species richness predictions and rough probabilities from SDM s, and a ‘trait range’ rule that uses the predicted upper and lower bound of community‐level distribution of three different functional traits (vegetative height, specific leaf area, and seed mass) to constrain a pool of species from binary SDM s predictions. Results We showed that all independent constraints contributed to reduce species richness overprediction. Only the ‘probability ranking’ rule allowed slight but significant improvements in the predictions of community composition. Main conclusions We tested various implementations of the SESAM framework by integrating macroecological constraints into S‐ SDM predictions, and report one that is able to improve compositional predictions. We discuss possible improvements, such as further understanding the causality and precision of environmental predictors, using other assembly rules and testing other types of ecological or functional constraints.

Tracking the expansion of the American mink (Neovison vison) range in NW Portugal - Diana C. Rodrigues; Luciana Simões; Jacinta Mullins; Simone Lampa; Raquel C. Mendes; Carlos Fernandes; Rui Rebelo; Margarida Santos-Reis (Biological Invasions, 2015)

A novel downscaling approach to predict plant invasions and improve local conservation actions - Rui F. Fernandes; Joana R. Vicente; Damien Georges; Paulo Alves; Wilfried Thuiller; João P. Honrado (Biological Invasions, 2014)

Cross-Talk Between Neurons and Astrocytes in Response to Bilirubin: Adverse Secondary Impacts - Ana Sofia Falcão; Rui F. M. Silva; Ana Rita Vaz; Cátia Gomes; Adelaide Fernandes; Andreia Barateiro; Claudio Tiribelli; Dora Brites (Neurotoxicity Research, 2014)

High antimicrobial activity of VLC isolated fractions from Bifurcaria bifurcata - Horta Andre; Pandeirada Raquel; Fernandes Lurdes; Alves Celso; Pinteus Susete; Silva Joana; Pedrosa Rui (Frontiers in Marine Science, 2014)

LEDs light spectrum effect on the success of fragmentation and growth of the leather coral Sarcophyton spp. - Fernandes Cátia; Mendes Catarina; Moreira André; Chambel João; Rocha Rui; Leandro Sergio; Pedrosa Rui (Frontiers in Marine Science, 2014)

Development of flange and reticulate wall ingrowths in maize (Zea mays L.) endosperm transfer cells - Paulo Monjardino; Sara Rocha; Ana C. Tavares; Rui Fernandes; Paula Sampaio; Roberto Salema; Artur da Câmara Machado (Protoplasma, 2013)

Imbalanced circulating matrix metalloproteinases in polycystic ovary syndrome - Valéria A. Gomes; Carolina S. Vieira; Anna L. Jacob-Ferreira; Vanessa A. Belo; Gustavo M. Soares; Janaína B. F. Fernandes; Rui A. Ferriani; Jose E. Tanus-Santos (Molecular and Cellular Biochemistry, 2011)

The selective COX-2 inhibitor Etoricoxib reduces acute inflammatory markers in a model of neurogenic laryngitis but loses its efficacy with prolonged treatment - Manuel Lima-Rodrigues; Nuno Lamas; Ana Valle-Fernandes; Andrea Cruz; Artur Vieira; Pedro Oliveira; Jorge Pedrosa; António G. Castro; Rui M. Reis; Fátima Baltazar; Armando Almeida (Inflammation Research, 2010)

Effect of chronic supplementation with shark liver oil on immune responses of exercise-trained rats - Daniele Cristina Vitorino; Cosme Franklim Buzzachera; Rui Curi; Luiz Claudio Fernandes (European Journal of Applied Physiology, 2010)

Cytochemical and ultrastructural study of anoikis and secondary necrosis in enterocytes detached in vivo - Ana do Vale; Carolina Costa-Ramos; Daniela S. P. Silva; Paula M. Macedo; Rui Fernandes; Paula Sampaio; Nuno M. S. dos Santos; Manuel T. Silva (Apoptosis, 2007)

Differential expression of proliferative, cytoskeletal, and adhesive proteins during postnatal development of the hamster submandibular gland - Rui P. Fernandes; Douglas A. Cotanche; Kelley Lennon-Hopkins; Fatih Erkan; A. Sue Menko; M. A. Kukuruzinska (Histochemistry and Cell Biology, 1999)